Indicators and Soil Management Options for Sustainable Agriculture under Practice Planning - Balaguravaiah, D.; Reddy, T. Yellamanda; Subramanyam, A.; Adinarayana, G. (Journal of Soil and Water Conservation, 2022)
Land degradation in the semiarid tropics of India affects 50% of its geographical area. Anantapur district that consists of 80% of red sandy loam soils besides poor in nutrients are often subjected to soil erosion. A survey to know the perceptions about sustainability among the rural farmers of Anantapur revealed interesting results. Able to produce good crop ranked first among sustainability indicators. Non availability of organic manures including green leaf manure remained a constraint due to climatic situation and social habits. Among various management options studied, addition of FYM + formation of dead furrows and surface covering with Glyricidia loppings are found good for reducing soil and water losses and increasing the crop yields. Encouraging agro forestry/ social forestry/community forestry perhaps may be the solution to produce organic matter in required quantities for use in agriculture and improving productivity